2022
DOI: 10.1021/acssuschemeng.2c05495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Lignin Structure on the Physicochemical Properties of Lignin-Grafted-Poly(ε-caprolactone) and Its Application for Water/Oil Separation

Abstract: Lignin-grafted poly(ε-caprolactone) copolymers (lignin-g-PCLs) have shown wide application potentials in coatings, biocomposites, and biomedical fields. However, the structural heterogeneity of lignin affecting the structures and properties of lignin-g-PCL has been scarcely investigated. Herein, kraft lignin is fractionated into four precursors, namely, Fins, F1, F2, and F3, with declining molecular weights and increased hydroxyl contents. Lignin-g-PCLs are synthesized via ring-opening polymerization of ε-capr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…The special free energies of methanol adsorption were determined using shell polymers POF-ET and POF-S� O (Figure 3C−D). The free energy of methanol adsorption (−ΔG methanol Sp ) of POF-S�O is higher (5.11 kJ/mol) than that of POF-ET (3.41 kJ/mol), indicating a stronger affinity for polar molecules, 47,50,51 highly due to the hydrogen bond (1.7 kJ/mol) between the OH group and the surface S�O groups (Table S2). Furthermore, an in situ DRIFTS study of alcohol adsorption was applied to show the interaction of OH groups with the catalyst shell.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The special free energies of methanol adsorption were determined using shell polymers POF-ET and POF-S� O (Figure 3C−D). The free energy of methanol adsorption (−ΔG methanol Sp ) of POF-S�O is higher (5.11 kJ/mol) than that of POF-ET (3.41 kJ/mol), indicating a stronger affinity for polar molecules, 47,50,51 highly due to the hydrogen bond (1.7 kJ/mol) between the OH group and the surface S�O groups (Table S2). Furthermore, an in situ DRIFTS study of alcohol adsorption was applied to show the interaction of OH groups with the catalyst shell.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The incorporation of SO and ethyl groups also results in different surface properties. According to the water contact angles of POF-ET (97°) and POF-SO (∼0°) (Figure S7), it could be observed that the significant difference in the wettability of the two materials is due to the functional group difference. Meanwhile, inverse-phase gas chromatography (IGC) was employed to characterize the surface energy of the shell to reflect their organophilic properties quantitatively. , Several n -alkanes served as the probe molecules to calculate the dispersive surface energy (γ S D ) (Supporting Note 1). POF-ET with a larger γ S D (22.8 mJ/m 2 ) is more organophilic (Table S2), whereas POF-SO displays a smaller γ S D value (15.3 mJ/m 2 ). , …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the DP influenced the initiation temperatures of degradation. 20,24 The initial decomposition temperature decreased from 341 to 328 °C when DP decreased from 101 to 22. In this case, the highest and lowest onset temperatures were found for PCL (371.63 °C) and LN (318.47 °C), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A trend emerged, showing that as the length of PCL arms increased, the T m of the copolymers approached the T m of PCL. 13,15,20,24 Crystallinity, as measured by DSC, displayed a slight decrease with an increase in the DP of PCL attached to LN. Previous studies either reported an increase in crystallinity with DP 20,22 or no trend.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally, there are two kinds of materials used in the oil-water separation process: one is superhydrophobic oleophilic material [4][5][6][7][8], this material is used in the case of oil and water separation of density than water, it cannot be separated from the density of oil than water; the other is superhydrophilic underwater oleophobic material [9][10][11][12][13], similar to this material is used in the case of density than water and water separation, it cannot be separated from the density of oil than water. Xie et al [14] obtained lignin-g-PCL by ring-opening polymerization of ε-caprolactone with lignin and investigated the thermal stability, hydrophobicity and UV-blocking ability. In the oilwater separation experiments, it was found that the lignin-g-PCL coated filter paper could successfully separate chloroform, petroleum ether and hexane-water mixtures with an efficiency of 99.2%.…”
Section: Introductionmentioning
confidence: 99%